PENGARUH LANGSUNG DAN TIDAK LANGSUNG KINERJA LINGKUNGAN PADA NILAI PERUSAHAAN - Lingga, Winayaka; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2017)
Good corporate value is one of the goals to be achieved by the company. The value of the firm is the perception of investors to the company that is often associated with corporate stock prices. The value of the company will be guaranteed to grow sustainably if the company takes into account the economic, social and environmental dimensions because sustainability is a balance between economic, community and environmental interests. The performance of corporate managers is expected not only to maximize the value of the company but also to have business in the framework of environmental awareness, such as reducing greenhouse emissions, minimizing environmental pollution, and using renewable alternative energy.   This study aims to find out directly and indirectly. This research uses quantitative approach with associative explanation level. This study uses quantitative approach with associative explanation level. The population in this study is a manufacturing company listed on the Stock Exchange period 2012-2014. Number of samples 34 companies with purposive sampling technique. Data analysis used in this research is path analysis (path analysis). This study found that environmental performance has a positive effect on firm value. Environmental performance does not indirectly affect company value through environmental disclosure. This suggests that environmental disclosure is not a mediating variable of the relationship between environmental performance and firm value.